Synthesis and Characterization of Dual-doped (Al, Co) ZnO Nanofibers for Sustainable Piezoelectric Nanogenerator Applications - Tauvana, Ade Irvan; Nulhakim, Lukman; Nurfadillah, Elsa (Piston: Journal of Technical Engineering, 2026)
This study reports the structural and morphological enhancement of aluminum (Al) and cobalt (Co) co-doped ZnO nanofibers synthesized via electrospinning for piezoelectric applications. The morphology and elemental composition were systematically analyzed using Scanning Electron Microscopy coupled with Energy-Dispersive X-ray Spectroscopy (SEM–EDX), while crystallographic properties were evaluated by X-ray Diffraction (XRD). SEM analysis revealed that the electrospun Al–Co co-doped ZnO nanofibers formed a highly interconnected and porous fibrous network with a uniform diameter distribution and negligible agglomeration, exhibiting diameters of 100–200 nm. EDX results confirmed the successful incorporation of Al and Co dopants into the ZnO matrix without detectable impurities. XRD patterns indicated a well-defined hexagonal wurtzite crystal structure with high crystallinity and a pronounced preferred orientation. The crystallite size, calculated using the Scherrer equation, ranges from 84 to 106 nm. The variation in crystallite size among different diffraction peaks is mainly attributed to differences in peak broadening (FWHM), which may indicate anisotropic crystallite growth and varying degrees of lattice orderingIn addition, the microstrain increased from 1.5 × 10⁻⁴ to 3.8 × 10⁻⁴, suggesting lattice distortion induced by Al³⁺ and Co²⁺ substitution. These findings demonstrate that Al–Co co-doped ZnO nanofibers possess favorable structural characteristics for advanced piezoelectric material development.